Kemampuan Tanaman Karet Dalam Menurunkan Kadar Dust Fall Di Sekitar Jalan Angkutan Batubara - Vista Septiani Putri; Junaidi Junaidi; Munawar Raharja (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
The Ability Rubber Plants in Lowering to Dust Fall Level Along the Coal Haul Road.Changes in air environment are generally caused by air pollution. Coal transportasion activity make the impact of air pollution such as dust fall along the coal haul road. A solution to handling dust fall along the coal haul road with vegetation of plant which have ability to reduce dust fall particles. The purpose of this research is to know the ability rubber plants in lowering the dust fall level along coal haul road. The benefit as raw material inputs in controlling of dust pollution in environment using berrier plant. The method of this research use a field experiment with design pretest and posttest with control group. The population of this research is the dust fall level and samples research is dust that measured on 4 location that represent the diffrences landscape 50 m, 100 m, 150 m and 200 m. Every width of landscape measure of 2 samples poin before and after of a landscape. It done in 5 times replicas.Data analysis using a simple regression. There is influence of rubber plant ability to decrease dust content to the distance determined with result of percentage of degradation of dust settled at 50 meter distance without barrier 48,0% to distance 50 meter with barrier 57,0%.